The effect of morphine on orthodontic tooth movement in rats - Akhoundi Mohammad S.A; Dehpour Ahmad Reza; Rashidpour Mahsa; Alaeddini Mojgan; Kharazifard Mohammad Javad; Noroozi Hassan (Sciendo, 2023)
To investigate the effect of morphine as an exogenous opioid on orthodontic tooth movement. Naltrexone will be used as an opioid antagonist to confirm the results.